Analysis of the Level of Trust of Students of Universitas Muhammadiyah Makassar towards the Security of Using Qris (Quick Response Code Indonesian Standard) as a Digital Exchange Tool - Husnaeda; A. Ifayani Haanurat; Andi Mappatompo (IECON: International Economics and Business Conference, 2025)
The development of information and communication technology, especially in digital payment systems, has changed the way financial transactions are conducted in Indonesia. Quick Response Code Indonesian Standard (QRIS), introduced by Bank Indonesia in 2019, has become one of the popular innovations among students. This study aims to analyze the level of trust of Muhammadiyah Makassar University students in the security of using QRIS as a digital currency. The research method used is a qualitative approach with in-depth interviews and observations of students who have used QRIS. The results showed that students have a fairly high level of trust in QRIS, which is influenced by practicality factors, service provider reputation, and the influence of the social environment. Despite concerns regarding security risks, students tend to see QRIS as a safe and efficient payment solution. In conclusion, to increase user trust, continuous education and socialization regarding the security and benefits of QRIS are needed.